SAT0715 Clinical significance of fibromyalgia syndrome in different rheumatic diseases: relation to disease activity and quality of life. (15th June 2017) - Gheita, TA; El-Rabbat, SM; Mahmoud, NK
Abstract : Background: In clinical practice, the co-expression of fibromyalgia syndrome (FMS) and a rheumatologic disease deserves special attention as FMS may go unrecognized especially when it develops after the disease or more commonly when it is misdiagnosed as an autoimmune disorder. Objectives: The aim of the present work was to compare the frequency of FMS in rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and Behçets disease (BD) patients and to study the relation of FMS to the clinical manifestations, laboratory features, disease activity and/or damage as well as the quality of life (QoL). Methods: One hundred and sixty patients (50 RA, 50 SLE, 30 SSc and 30 BD) consequently recruited from those attending the Rheumatology outpatient clinic and department, Faculty of Medicine, Cairo University Hospital. and 141 age and sex matched corresponding healthy controls were included. Disease activity was assessed using Disease Activity Score in 28 joints (DAS28) for RA, SLE Disease Activity index (SLEDAI), modified Rodnan skin score for SSc and BD Current Activity Form (BDCAF). The Systemic Lupus International Collaborating Clinics (SLICC)/ACR damage index was assessed in SLE patients. The quality of life (QoL) was also recorded. Severity in FMS cases was estimated using the revised Fibromyalgia Impact Questionnaire (FIQ) score. Results: In the RA, SLE, SSc and BD patients, FMS was found in 14%, 18%, 6.67% and 3.33% respectively compared to 2.1%, 3%, 3.3% and 0% in their corresponding controls. In RA patients, DAS28 was significantly higher in those with FMS (5.5±0.9) compared to those without (4.3±1.3) (p=0.009); significantly correlated with both Widespread Pain Index (WPI) (p=0.011) and Symptom Severity (SS) scale (p=0.012) and the QoL scale in those with FMS was significantly worse (62.3±7.9) compared to those without (71.7±14.4) (p=0.023). In SLE patients, The WPI and SS both significantly correlated with the presence of thrombosis (r=0.28, p=0.049 and r=0.43, p=0.002 respectively). The SS scale tended to correlate with the SLEDAI (r=0.28, p=0.05). In BD patients, BDCAF and WPI significantly correlated (p=0.03). On comparing the WPI among the rheumatic diseases patients, the mean was significantly higher in the SLE patients (2.3±3.2) compared to that in the RA (1.96±2.6), SSc (1.9±2.2) and BD (0.7±1.1) patients (p=0.047). Conclusions: Fibromyalgia syndrome is more frequent in rheumatic diseases. The significance of this study is boosted by the fact that it was among the first to investigate the prevalence of FMS in patients with SSc. Also, adds to the limited insights on the relation of FMS to BD. It is novel to present the relative prevalence of FMS in different Egyptian rheumatic diseases patients and to throw light on the association with disease activity in RA and BD as well as thrombosis in SLE. The impact of FMS on the QoL in RA patients requires special attention. Disclosure of Interest: None declared